A Novel Method to Prepare PolyGMA and its Application to Immobilization of β-Galactosidase - Sun Sufang; Dong Lingyun (E-Journal of Chemistry)
The reactive, macroporous and massive epoxy group containing polyGMA was synthesized simultaneously with methanol aqueous solution and nano-calcium carbonate as porogen by bulk copolymerization. After the polymer was smashed, particles with diameters in the range of 0.30 to 0.45 mm were taken as the carrier and the scanning electron microscopy (SEM) micrographs were done to characterize its surface structure. Under the optimum conditions, β-galactosidase was immobilized on the supporter obtained above and the enzyme activity bound per gram drier carrier could attained up to 77.33％, which was much higher than that bound on the carrier prepared by only using methanol aqueous solution as porogen. The conclusion obtained indicated that the ployGMA prepared concurrently with liquid and solid porogen was more suitable to immobilize enzyme because of the much more porous surface structure obtained.